2021
DOI: 10.31234/osf.io/fbj9g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability and feasibility of an online psychosocial intervention for Dutch adolescents with a visible difference: a mixed-methods study

Abstract: Introduction: Adolescents with a visible difference can experience difficult social situations, (e.g., people staring or making unwanted comments) and are at risk for mental health problems. Unfortunately, interventions for adolescents with a visible difference who experience appearance-related distress are scarce and lack an evidence-base. This study tests the acceptability and feasibility of YP Face IT, an innovative online psychological intervention, in Dutch adolescents. Methods: Adolescents aged 12-18 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Second, some adolescents mentioned that YPF could be perceived as somewhat childish. This was reported also in van Dalen et al 29 and Riobueno-Naylor et al, 28 who suggested tailoring the content to older adolescents. Based on our findings, developing a simpler and less time-consuming version of the programme, possibly for younger adolescents, should alternatively be considered.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Second, some adolescents mentioned that YPF could be perceived as somewhat childish. This was reported also in van Dalen et al 29 and Riobueno-Naylor et al, 28 who suggested tailoring the content to older adolescents. Based on our findings, developing a simpler and less time-consuming version of the programme, possibly for younger adolescents, should alternatively be considered.…”
Section: Discussionsupporting
confidence: 63%
“…14 Other features of YPF that were mentioned as possibly less useful, were the discussion forum and the journal, in line with previous pilot studies. 20,29 For future implementations of YPF, a plan for how to continually update and improve the programme seems paramount to maintain its relevance and acceptability.…”
Section: Contributions Of Ypf: Validation and Positive Changesmentioning
confidence: 99%
“…Several studies across the world have explored the feasibility and acceptability of the intervention van Dalen et al, 2021b), and YPF consequently exists in English (https://www.ypfaceit.co.uk), Norwegian (https://www.ungfaceit.no/), and Dutch (https://www.faceitvoorjongeren.nl/). The British version of YPF was evaluated in a feasibility trial by and was delivered to adolescents with a wide range of conditions leading to a visible difference.…”
Section: Figurementioning
confidence: 99%
“…indicating that the intervention could improve body esteem and reduce social anxiety . Similarly, the Dutch version of YPF was evaluated in an acceptability and feasibility study, but without the use of a randomisation procedure and a control group (van Dalen et al, 2021b). Adolescents generally found that YPF was relevant and contained pertinent techniques and stated that the intervention had made a positive impact on them and that they would recommend YPF to other adolescents with a visible difference.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation